Recent advances in electrospun fibrous membranes for effective chromium (VI) removal from water - Mohammed, Aveen Mustafa; Thalji, Mohammad R.; Yasin, Suhad A.; Shima, Jae Jin; Chong, Kwok Feng; Guda, Alexander A.; Ali, Gomaa A.M. (Elsevier B.V., 2023)
The accumulation of heavy metals in aquatic environments is a significant environmental threat. Among the available methods for their removal, adsorption using nanofiber has been proven to be the most effective approach. The unique architecture of nanofibers provides them with intriguing features, such as high specific surface area and pore density, which makes them capable of removing harmful metals and a potential solution for various applications, including water treatment. This new generation of highly porous membranes is expected to have a promising future in separation applications due to its unique properties, including 90% porosity and 3D interconnected pore structure. Electrospinning is a well-regarded technique for creating such unique porous membranes. Among the various metal ions, chromium (Cr(VI)) removal has been extensively researched, and electrospun nanofiber membranes have proven to be an effective adsorbent. The objective of this review is to provide up-to-date information on the most common ways that electrospun nanofiber membranes are utilized for the removal of Cr(VI) ions from water. The findings indicate that electrospun fibrous materials are effective in eliminating Cr(VI) and establish their suitability for decontaminating polluted water. However, further attention is required to enhance the stability, mechanical strength, and reusability of these fibrous membranes.